ALAT UKUR KADAR KARBON MONOKSIDA (CO) PADA ROKOK - ., Riki Arya Pratama (Jurnal Teknik Elektro Universitas Tanjungpura, 2018)
In this research making a measuring instrument for carbon monoxide in cigarettes, which can determine the level of danger of carbon coming from cigarette smoke. Carbon monoxide measuring instrument consists of MQ 7 sensor, Arduino Uno, LED indicator, blower fan and programming using Arduino IDE. The software created works to display data in ppm units and turn on the indicator LED. ppm that finds from the lowest to the same time. Of the various types of cigarettes have different levels of ppm each, therefore, all types of cigarettes are basically very needed, the faster cigarettes with low ppm levels reach the level of ppm to high also for the human body.